The PHaVE List: a pedagogical list of phrasal verbs and their most frequent meaning senses - Garnier, Mélodie; Schmitt, Norbert (SAGE, 2015)
As researchers and practitioners are becoming more aware of the importance of multi-word items in English, there is little doubt that phrasal verbs deserve teaching attention in the classroom. However, there are thousands of phrasal verbs in English, and so the question for practitioners is which phrasal verbs to focus attention upon. Phrasal verb dictionaries typically try to be comprehensive, and this results in a very large number of phrasal verbs being listed, which does not help practitioners in selecting the most important ones to teach or test. There are phrasal verb lists available (Gardner and Davies, 2007; Liu, 2011), but these have a serious pedagogical shortcoming in that they do not account for polysemy. Research indicates that phrasal verbs are highly polysemous, having on average 5.6 meaning senses, although many of these are infrequent and peripheral. Thus practitioners also need guidance about which meaning senses are the most useful to address in instruction or tests. In response to this need, the PHrasal VErb Pedagogical List (PHaVE List) was developed. It lists the 150 most frequent phrasal verbs, and provides information on their key meaning senses, which cover 75%+ of the occurrences in the Corpus of Contemporary American English. The PHaVE List gives the percentage of occurrence for each of these key meaning senses, along with definitions and example sentences written to be accessible for second language learners, in the style of the General Service List (West, 1953). A users’ manual is also provided, indicating how to use the list appropriately.